Anticancer activity of lectins from bauhinia purpurea and wisteria floribunda on breast cancer MCF-7 cell lines - Agrawal, Sanskruthi B.; Gupta, Neha; Bhagyawant, Sameer S.; Gaikwad, Sushama M. (Protein and Peptide Letters, 2020)
Background: Individual and collaborative efforts are being made worldwide in search of effective chemical or natural drugs with less severe side-effects for treatment of cancer. Due to the specificity and selectivity properties of lectins for saccharides, several plant lectins are known to induce cytotoxicity into tumor cells. Objective: To study the antiproliferative activity of two N-acetyl galactosamine specific plant lectins from seeds of Bauhinia purpurea and Wisteria floribunda against MCF-7 Breast cancer cell lines. Methods: MTT, lactate dehydrogenase (LDH) leakage, reactive oxygen species (ROS), and caspase-3 assays and flow cytometry for cell cycle analysis were performed. Results: The agglutinins BPL and WFL; 446 mu gml(-1) (2.2 mu M) and 329 mu gml(-1) (2.8 mu M), respectively caused remarkable concentration-dependent antiproliferative effect on MCF-7. The effect was seen to be a consequence of binding of the lectin to the cell surface and triggering S and G2 phase arrest. Apoptosis induced was found to be associated with LDH leakage, cell cycle arrest and ROS generation. The apoptotic signal was observed to be amplified by activation of caspase-3 resulting in cell death. Conclusion: The study provides a base for detailed investigation and further use of lectins in cancer studies.
Keywords: anti-cancer; antiproliferative; Apoptosis; caspase-3; cell cycle arrest; Lectins; MCF-7; reactive oxygen species